Intersectionality and Disability An Analysis of Multiple Discrimination Against Women with Disabilities in Public Spaces in Surabaya - Diva Aisya Cherynata; Aura Dyka's Qurrota A'yun; Ayu Novia Rahmatillah; Tyas Mardiana; Muhammad Iqbal Panji Satrio (Universitas Negeri Surabaya, 2026)
This study examines intersectional discrimination experienced by women with disabilities in accessing urban public spaces in Surabaya. Urban development frequently prioritizes standardized infrastructure while neglecting the lived experiences of marginalized groups, thereby producing exclusionary environments. This research aims to analyze how the intersection of gender and disability influences accessibility, safety, and socio-spatial experiences in public transportation and urban parks. A qualitative descriptive-analytical design was applied, with data collected through in-depth interviews and field observations and analyzed using thematic analysis to identify patterns of physical, sensory, and social barriers. The findings indicate that women with disabilities encounter multiple and interconnected challenges, including inadequate infrastructure such as unsafe ramps and damaged guiding blocks, insufficient lighting that increases vulnerability, and persistent social stigma. These barriers limit mobility, reduce independence, and contribute to heightened perceptions of insecurity. The study further demonstrates that accessibility is closely associated with safety, as inadequate environmental design and limited social protection intensify exposure to discrimination and potential violence. In conclusion, intersectional discrimination in urban spaces is embedded in structural inequalities shaped by ableism and patriarchy, requiring an integrated approach that combines inclusive infrastructure, social awareness, and participatory policy implementation.